Dynamic Cost of Cooling, Heating and Power in Integrated Energy System Based on Exergy Economics - Jinbu LIAN; Ling ZHANG; Xiao GAO; Chengren LI; Yongqiang LUO; Zhongbing LIU (Zhongguo dianli)
Cost allocation of integrated energy systems (IES) with multi-energy flow coupling is a key technical issue in the study of integrated energy services. Existing cost calculations of IES products do not take into account the effect of energy grade, and no in-depth study has been carried out on the cost variations of IES with energy storage. A dynamic exergy economics model of IES is established based on the second law of thermodynamics to study the influence of dynamic load and energy storage on the cost of cooling, heating and power of a park IES. The results show that the thermal storage device can effectively reduce the unit cost of cooling, heating and power; compared with the IES without thermal storage, the IES with thermal storage can reduce the unit cost of cooling, heating and power by 6% , 24% and 1.2%, respectively; and the average cost of cooling, heating and power of IES under thermal storage condition is positively correlated with the electric load, and negatively correlated with the heating and cooling load. The dynamic exergy economics model can efficiently analyze the hourly cooling, heating and power cost of IES with heat storage in the optimization period, and provide a basis for the real-time pricing of cooling, heating and power. The rational use of energy storage device can reduce the cost of cooling, heating and power products, contribute to internal combustion engine absorption, and improve the stability and economy of the system operation.